(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the functional outcome of open Latarjet procedure for recurrent anterior shoulder dislocation. Methods: This descriptive study was conducted in Department of Orthopaedics, Lahore General Hospital Lahore from 21st January 2019 to 29th December 2020. All adults patients of recurrent anterior shoulder dislocation fulfilling the inclusion criteria were operated with open Latarjet procedure. Functional outcome was assessed with Constant-Murley shoulder score at 6th months and rated as very good outcome (86-100 score), good outcome (71-85 score), fair outcome (56-70 score) and poor outcome (< 56 score). Comparative analysis of important outcome variables was done with paired-t test and P value < 0.05 was considered significant. Results: The total number of patients were 35. There were 34 (97.14%) male and 1(2.85%) female. The mean age of our patients was 48.4±9.0 years. Right side was involved in 26(74.28%) and left in 9(25.71%). At 6th month postoperatively very good outcome was noted in 23(65.71%), good in 8(22.85%), fair in 2(5.71%) and poor outcome in 2(5.71%) patients. Significant pain reduction and improved range of shoulder motion was documented at 6th month. (P value < 0.05). Conclusion: Open Latarjet technique is a reliable and safe option for recurrent anterior shoulder dislocation as very good functional outcome was achieved in majority of our patients.